Epidemiological Profile of Snakebite in Iran, 2009-2010 Based on Information of Ministry of Health and Medical Education - Dehghani, R; Dadpour, B; Mehrpour, O (International Journal of Medical Toxicology and Forensic Medicine, 2014)
Background: Snake bite is one of the significant health problems in the tropical and subtropical regions. It is a common medical emergency in Iran. The current study was conducted to characterize related risk factors for snake bite accidents. Methods: This research was a descriptive retrospective study. Data were collected by gathering snake bite records of 42 Medical Sciences Universities in Iran from March 2009 to March 2010. Information included: age and sex of the victims, region of incident, site of bite and outcome. Results: The results showed that the majority of snake bite patients were male (66.1%). The age distribution of patients indicated that the greatest rate of snake bites occurred among the 25-34 years old. Of 5172 snake bite, 2851 (54.7%) observed on lower limbs, 12019 (38.9%) on upper limbs and 303(5.8%) on head and Trunk and 20 (0.3%) unknown site. The average incidence of snake bite was estimated 6.9 Per 100,000, however, the highest and the lowest affected cases were observed in Semnan province (with incidence of 111.6 per 100000 individuals) and Rafsanjan, Sabzevar cities (with incidence of 0 per 100000), respectively. The mortality and recovery rates of cases with and without anti venom, was evaluated (0.12%, 99.88%) and (0.4%, 99.6%) respectively. Conclusion: The high incidence of snake bites in some of provinces of Iran suggests the necessity of preventive programs for minimizing the incidence. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->